Influence of processing parameters on physical properties of fish feed pellet prepared using steaming method - Mohd Zaki, Nor Nadiha; Idris, M.H.H.; Mohd Hashim, Amalia; Manaf, Yanty Noorzianna; Mohd Desa, Mohd Nasir; Yuswan, Mohd Hafis; Abdullah Sani, Muhamad Shirwan; Kamaruddin, Mohd Salleh; Hassan, M.S (Animal Nutrition Association, 2022)
Uncertainty in the origin of raw materials used in the fish pellet prompts homemade preparation by certain farmers. We hypothesized that a combination of optimum processing conditions will produce pellets with desirable physical properties. In this study, a cost-saving protocol for manual preparation of Clarias gariepinus feed pellet was developed. The objective of this study was to investigate the effect of different processing conditions on the physical properties of the fish pellets produced by steaming method. Proximate analysis of each ingredient was measured, and feed formulation was calculated using WinFeed 2.0 software. Twenty-seven processing conditions with different processing temperatures (50°C, 70°C and 100°C), mixing speeds (75 rpm, 150 rpm, and 225 rpm), and mixing times (5 min, 10 min, and 15 min) were tested. Floatability, bulk density, water solubility index (WSI), and water absorption index (WAI) were then determined. There were also significant interactions between physical properties and all processing conditions, except time/speed. Processing conditions at 70°C, mixing speed at 75 rpm and 5 min-of mixing time showed the highest pellet floatability (15 min) followed by 50°C and 100°C. Bulk density, WAI, and WSI were also improved, suggesting that at 70°C, proper gelatinization may have occurred. This study presented the optimum parameters for manual fish pellet preparation using the steaming method and is expected to economically benefit small-scale farmers to produce fish pellets in situ.